Penggunaan Herbal Balm Aromaterapi Essential Oil Bunga Lavender Sebagai Pencegahan Insomnia Usia Produktif di Universitas Aisyiyah Yogkakarta : Indonesia - Faridah, Imaniar Noor; Pertiwi, Deasy Vanda; Hipmi, Ahmad Fahrian; Maulizah, Rizlah; Rahmawati, Sri (UII, 2025)
One of the basic human needs is sleep, every individual definitely needs enough sleep between 6-9 hours a day. The benefits you get from getting enough sleep include maintaining stamina and health. According to the World Health Organization (WHO), in Indonesia in 2020 around 10%, which means approximately 28 million of the totals 238 million Indonesian population suffer from insomnia. Insomnia is a symptom of difficulty sleeping which is usually caused by bad behavior or habits before bed. In general, teenagers often experience insomnia due to consuming too much caffeine (coffee). The aim of this empowerment program activity is to provide more knowledge regarding insomnia and making lavender essential oil aromatherapy balm to help reduce insomnia that occurs among students, especially at Aisyiyah University, Yogyakarta, as well as increasing student creativity. in entrepreneurship. The implementation method was carried out by counseling about insomnia and the practice of making aromatherapy balm as an alternative treatment for insomnia at Aisyiyah University, Yogyakarta. Making aromatherapy balm preparations using an inhalation mechanism is very effective and easy to apply while traveling. The results of data analysis from giving questionnaires to students regarding insomnia knowledge showed that the score at the pretest was 50% (poor category), and the posttest had a score of 76.8% (good category). The results of this analysis showed that there was a significant difference in scores before and after giving the counseling. insomnia in productive age at Aisyiyah University Yogyakarta. Aromatherapy balm therapy as an alternative to reduce insomnia. Lavender aroma therapy contains linalool acetate which is able to relax and relax the nervous system and tense muscles by increasing the frequency of alpha waves and this condition is associated with treating insomnia.